ANALISIS EFEKTIVITAS PERAN ALTERNATIF PENYELESAIAN SENGKETA (ADR) SEBAGAI SOLUSI DI LUAR PENGADILAN - Yunita Sari, Kamelia; Ahyar Wiraguna, Sidi (Penerbit Lafadz Jaya, 2026)
The Indonesian judicial system faces significant challenges from prolonged litigation processes, high costs, and administrative complexities, resulting in a backlog of 5.2 million cases in 2023. This study aims to analyze the effectiveness of Alternative Dispute Resolution (ADR) as a non-litigation solution, focusing on its concepts, legal basis, and implementation. Employing a normative legal research method with statutory, conceptual, and comparative approaches, the population comprises Indonesian ADR regulations and doctrines, while the purposive sample includes 45 sources from 2021-2025. Data collection utilized library research from Google Scholar and official institutions, analyzed through descriptive-analytical qualitative techniques. Results indicate ADR reduces caseloads by 42% via mandatory mediation (PERMA No. 1/2016), achieves 30-day resolutions versus years in litigation, and cuts costs by 30%, though hindered by low public awareness and mediator shortages. In conclusion, ADR proves effective for substantive justice but requires regulatory strengthening and digitalization for optimal implementation.